2017
DOI: 10.21873/anticanres.11346
|View full text |Cite
|
Sign up to set email alerts
|

Complex of Platinum(II) with Tris(2-carboxyethyl)phosphine Induces Apoptosis in Canine Lymphoma/Leukemia Cell Lines

Abstract: The cis-[PtCl(TCEP)] seems to be a potent anticancer agent, although further investigations are necessary to elucidate its biological activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…The anti-tumor effects of BA and BT were to some extent related to inhibited cell proliferation. Additionally, CLBL-1 line was the most sensitive to BA (the lowest IC 50 for BA in all three cell lines), which was concurrent with previous studies (26)(27)(28). It was suggested that B-cell lymphoma may be more sensitive to BA-based treatments.…”
Section: Discussionsupporting
confidence: 85%
“…The anti-tumor effects of BA and BT were to some extent related to inhibited cell proliferation. Additionally, CLBL-1 line was the most sensitive to BA (the lowest IC 50 for BA in all three cell lines), which was concurrent with previous studies (26)(27)(28). It was suggested that B-cell lymphoma may be more sensitive to BA-based treatments.…”
Section: Discussionsupporting
confidence: 85%
“…Nevertheless, the Pt‐TCEP was shown to have a considerably higher inhibitory effect than cisplatin on cell viability in canine and human OSA cell lines. This is in accordance with a previous study on canine leukaemia and lymphoma cell lines, in which the new compound was several times more effective than cisplatin in inducing cell apoptosis and death . Additionally, comparing the results of MTT assay with analysis of apoptosis level in the same concentrations and time of incubation, it can be concluded that at the lower concentrations the compound has mainly cytostatic effect, and with its increase, the reduction of cell viability is related to apoptosis as it is in the case of other platinum‐based drugs .…”
Section: Discussionsupporting
confidence: 90%
“…The study revealed that this agent was far more active in these cell lines in comparison to cisplatin. It was also confirmed that apoptosis was responsible for the observed cell death …”
Section: Introductionmentioning
confidence: 61%
“…Recently, a new platinum-based compound containing a phosphine ligand tris(2-carboxyethyl)phosphine [P(CH 2 CH 2 COOH) 3 ] (TCEP) instead of ammonium group and two chlorine atoms in cis and trans conformation with potential anticancer activity has been introduced. The phosphane complexes exhibit cytotoxic activity against cisplatin resistant tumor cells and sometimes are more active than cisplatin (Pruchnik et al 2015 ; Henklewska et al 2017 ). Newly obtained platinum(II) complex with tris(2-carboxyethyl)phosphine (TCEP): cis -[PtCl 2 (TCEP) 2 ], which is the subject of this research exhibits interesting reactivity in solutions (Pruchnik et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%